2005
DOI: 10.1016/s1472-6483(10)60837-1
|View full text |Cite
|
Sign up to set email alerts
|

Highly efficient vitrification method for cryopreservation of human oocytes

Abstract: Two experiments were performed to develop a method to cryopreserve MII human oocytes. In the first experiment, three vitrification methods were compared using bovine MII oocytes with regard to their developmental competence after cryopreservation: (i) vitrification within 0.25-ml plastic straws followed by in-straw dilution after warming (ISD method); (ii) vitrification in open-pulled straws (OPS method); and (iii) vitrification in <0.1 microl medium droplet on the surface of a specially constructed fine polyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

16
714
2
42

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 1,071 publications
(779 citation statements)
references
References 35 publications
16
714
2
42
Order By: Relevance
“…In fact, after approximately 20 years of efforts in basic and clinical research [1,2,4,14,15,[27][28][29][30][31], oocyte cryopreservation has been described to achieve high standards of clinical efficiency [3,6,7,32]. Objective clinical evidence is emerging at a relatively slow pace, because IVF centres that routinely cryopreserve oocytes are still few and, consequently, current data are too small or dishomogeneous to draw definitive conclusions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In fact, after approximately 20 years of efforts in basic and clinical research [1,2,4,14,15,[27][28][29][30][31], oocyte cryopreservation has been described to achieve high standards of clinical efficiency [3,6,7,32]. Objective clinical evidence is emerging at a relatively slow pace, because IVF centres that routinely cryopreserve oocytes are still few and, consequently, current data are too small or dishomogeneous to draw definitive conclusions.…”
Section: Discussionmentioning
confidence: 99%
“…Comparing fresh oocytes with others frozen with a CRSC involving 0.1 mol/l sucrose as an extracellular CPA, Ghetler et al [36] found massive reduction in the number of CG as a effect of cryopreservation, concluding that stored oocytes should be microinjected rather than inseminated by standard IVF to prevent possible fertilization failure secondary to zona hardening. In effect, ICSI (intracytoplasmic sperm injection) had been suggested to be the elective route to achieve fertilization in cryopreserved oocytes [27] and has now become a standard of treatment [6,7,14,29]. The question of a nonphysiological discharge of CG in cryopreserved oocytes remains controversial.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the intervening years, variations to OC methods including changes in sucrose [14][15][16] and sodium [17,18] concentrations in slow freezing media, along with the first report of successful oocyte vitrification [19] and the development of novel cryotools [20][21][22][23] have combined to provide consistently improved survival and pregnancy rates with OC. In addition, although depolymerization of the oocyte's meiotic spindle is known to occur, a number of studies have now shown that the spindle reforms in the majority of oocytes after thawing [24][25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…Treatment with CPA induced a transient rise of intracellular free calcium level, premature exocytosis of cortical granules, and hardening of zonae pellucidae [7,8]. Application of vitrification improved the efficacy of oocyte cryopreservation, especially in mice [9,10] and humans [11,12]. However, vitrification of oocytes from large domestic species enriched with cytoplasmic lipid droplets still requires substantial improvement [13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%